2017
DOI: 10.3201/eid2301.161169
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus in Wild Boars and Spillover Infection in Red and Roe Deer, Germany, 2013–2015

Abstract: To determine animal hepatitis E virus (HEV) reservoirs, we analyzed serologic and molecular markers of HEV infection among wild animals in Germany. We detected HEV genotype 3 strains in inner organs and muscle tissues of a high percentage of wild boars and a lower percentage of deer, indicating a risk for foodborne infection of humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 15 publications
7
96
0
1
Order By: Relevance
“…In this study, we observed a median viral load of 10 7 GE/gr. This value is comparable to previous studies (Anheyer‐Behmenburg et al., ; Kamar et al., ). In the absence of in vitro cultivation, detection of HEV RNA does not confirm the viability of the virus.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, we observed a median viral load of 10 7 GE/gr. This value is comparable to previous studies (Anheyer‐Behmenburg et al., ; Kamar et al., ). In the absence of in vitro cultivation, detection of HEV RNA does not confirm the viability of the virus.…”
Section: Discussionsupporting
confidence: 92%
“…This study confirmed a wide heterogeneity of sequenced wild boar HEV strains that belonged to at least two subtypes HEV‐3c and HEV‐3f. The sequence analyses revealed that HEV‐3c is frequent, as observed in other studies conducted in both Italy and Europe (Anheyer‐Behmenburg et al., ; Aprea et al., ; Di Profio et al., ; Dorn‐In et al., ; Rutjes et al., , ; Schielke et al., ; Serracca et al., ; Thiry, Mauroy, et al., ; Vina‐Rodriguez et al., ). In Italy, HEV‐3c is less frequent detected in pigs, where the main subtypes are HEV‐3f and HEV3‐e.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The research carried out by different authors has shown that HEV can be identified in spleen tissue samples collected from domestic pigs, both in experimental (Lee, Ha, Ahn, & Chae, ; Williams et al., ) as well as in natural infections (Choi & Chae, ). Anheyer‐Behmenburg et al., ; detected RNA HEV in the spleen and also kidney tissues of wild boars and deer from Germany. Our results might reflect the suggestions from the literature indicating that HEV replicates and accumulates in tissues other than the liver (de Deus et al., ; Williams et al., ).…”
Section: Discussionmentioning
confidence: 99%